Delaying Injection of prostaglandin F2a in an ovsynch protocol - Portaluppi, M.A.; Tenhouse, D.E.; Stevenson, Jeffrey S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Our objective was to determine whether delaying the PGF2α injection by 24 or 48 hr after the first GnRH injection in an Ovsynch protocol (from a standard 7 days) altered ovar-ian characteristics in lactating dairy cows. Es-trous cycles were synchronized in 36 Hol-steins after removal of a progesterone-releasing controlled internal drug release (CIDR) insert and injection of PGF2α. On day 6 of the estrous cycle, cows were administered 100 μg of GnRH (81 ± 2 days postpartum) and assigned randomly to receive a treatment in-jection of PGF2α 7, 8, or 9 days later. Timed artificial insemination (TAI) was performed at 48 hr after PGF2α, at which time a second in-jection of GnRH was administered. Ovarian structures were mapped by ultrasonography on day 0 (first GnRH injection), on day 2 to de-termine responses to the first GnRH injection, at PGF2α injection, and daily thereafter through 72 hr after PGF2α to monitor ovula-tion of preovulatory follicles. Blood was col-lected on day 0, day 2, at PGF2α injection, and at 24 and 48 hr after PGF2α, to monitor serum changes estradiol-17ß and progesterone. On the basis of serum progesterone and ovarian exams, 2 cows were eliminated because of anestrus and their failure ovulate a follicle in response to the first GnRH injection. Two other cows in which luteolysis failed to occur after PGF2α treatment also were eliminated. Final numbers of cows per treatment were: 7 days (n = 13), 8 days (n = 9), and 9 days (n = 10). Twenty-nine of 32 cows ovulated (90.6%) in response to the first GnRH injec-tion. Despite a 24- or 48-hr delay between first GnRH and PGF2α injections, the diameter (mm) and volume (mm3) of the ovulatory fol-licle did not differ among treatments. In all 32 cows, at least 1 follicle ovulated after treat-ment, but ovulation rates did not differ. Serum concentrations of estradiol-17ß did not differ among treatments. Two cows in the 7-day treatment and 2 cows in the 8-day treatment were inseminated 24 hr late and were ex-cluded before assessing conception rates: 5/9 (55.6%), 5/9 (55.6%), and 1/10 (10%), respec-tively. We concluded that delaying PGF2α in-jection by 24 hr had little effect on outcomes.
Dairy Research, 2006 is known as Dairy Day, 2006
Keywords: Dairy; Follicle; Ovsynch; Ovulation; Pregnancy rate